Dynamic valgus knee revealed with single leg jump tests in soccer players - Uhlár, Á.; Ambrus, M.; Lacza, Z. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Dynamic valgus knee occurs in sports that involve jumps and landing such as soccer and pose an increased risk for anterior cruciate ligament injury. Visual estimation is biased by the athlete`s body type, the experience of the evaluator and the movement phase at which the valgus is assessed - thus the result is highly variable. The aim of our study was to accurately assess dynamic knee positions during single and double leg tests through a video-based movement analysis system. METHODS: Young soccer players (U15, N.=22) performed single leg squat, single leg jump, and double leg jump tests while the knee medio-lateral movement was monitored with a Kinect Azure camera. Jumping and landing phases of the movement were determined within the continuous recording of the knee medio-lateral position over the ankle and the hip vertical position. Kinect measurements were validated by Optojump (Microgate, Bolzano, Italy). RESULTS: Soccer players retained their predominantly varus knee positions in all phases of double-leg jumps, which was far less prominent in single leg tests. Interestingly, a marked dynamic valgus was observed in athletes who participated in traditional strengthening exercises, while this valgus shift was mostly prevented in those who participated in antivalgus training regimes. All these differences were only revealed during single leg tests, while the double leg jump tests masked all valgus tendencies. CONCLUSIONS: We propose to use single-leg tests and movement analysis systems for evaluating dynamic valgus knee in athletes. These methods can reveal valgus tendencies even in soccer players who have a characteristic varus knee while standing.